Cytotoxic Evaluation of Some Fused Pyridazino- and Pyrrolo-quinazolinones Derivatives on Melanoma and Prostate Cell Lines - Vaseghi, Golnaz (Adv Biomed Res, 2017)
BACKGROUND: Quinazolinon as an important class of heterocycles is attractive in medicinal research areas due to their wide range of biological effects. Cytotoxic activities of the quinazolinone derivatives in various cell lines including: HeLa, L1210 (mouse lymphocytic leukemia) and HT29 (human colon adenocarcinoma) were reported. MATERIALS AND METHODS: In this study, a number of newly made tricycles quinazolinone derivatives such as fused pyridazino-quinazolinones and fused pyrrolo-quinazolinones were evaluated on two cancerous cell lines, melanoma (B16F10) and prostate (PC3) using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide colorimetric assay. RESULTS: The results of cytotoxicity evaluations indicated that almost all of the compounds at the concentrations of 10 and 100 μM showed significant differences in viability in comparison with negative control at 48 h exposure (P < 0.05). However, during 24 h exposure some of the compounds showed cytotoxicity activity. CONCLUSION: Results showed that both cell lines were sensitive to synthesized compounds and longer duration of exposure (48 h) had better results compared to that of 24 h screening.